Professional values - an international basis for ethical issue? - Horvat, Aleksandra (Array, 2006)
The day to day circumstances of information professionals worldwide differ significantly, due to historical reasons and current developments in society. Yet, they are performing the same profession and have formulated codes of ethics, as listed on the IFLA /FAIFE website. Aware of a gap between the professional values stated in some new code of ethics and the real life situations the authors want to find out if professional values differ from state to state and if it is possible to speak of professional values as an international basis for ethical issues in librarianship. The research comprises surveys on professional values in two countries: Croatia and the Netherlands. Data were gathered by an electronic questionnaire on library discussion lists and websites of the library association, but traditional questionnaires printed and mailed by ordinary mail were also used. The research was based on international pre-surveys. Whereas in this latter survey, intellectual freedom, preservation of the record, equality of access and information literacy were listed as primary values for librarians and information professionals, the present research attempted to make a comparison between librarianship in the two countries in search of an international basis for ethical issues. The position and responsibility of information professionals confronted with international ethical issues such as defending the interests of readers and library users in the context of upcoming anti-terrorist and security legislation, as another side of the Network Society, was also discussed.